KOMPETENSI, MOTIVASI, TEKANAN ANGGARAN WAKTU, DAN KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT INSPEKTORAT - Ghina Fitri Ariesta Susilo (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The Inspectorate as the government's internal control apparatus is tasked with overseeing and guarding government programs. The implementation of the duties of the inspectorate is carried out by the auditor which makes the auditor must provide quality audit results. The method of writing this article uses an exploratory qualitative method with literature studies and documentation studies. The limitations of this research article are on the variables of competence, motivation, time budget pressure, and task complexity that affect audit quality in the scope of the Inspectorate. The purpose of this study was to see the effect of competence, motivation, time budget pressure, and task complexity on audit quality at the Inspectorate. The results of this study are competence has a positive effect on audit quality, motivation has a positive effect on audit quality, time budget pressure has a negative effect on audit quality, and task complexity has a negative effect on audit quality